2017
DOI: 10.1155/2017/7260130
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor, Depression, and Physical Activity: Making the Neuroplastic Connection

Abstract: Brain-derived neurotrophic factor (BDNF) is a neurotrophin that is vital to the survival, growth, and maintenance of neurons in key brain circuits involved in emotional and cognitive function. Convergent evidence indicates that neuroplastic mechanisms involving BDNF are deleteriously altered in major depressive disorder (MDD) and animal models of stress. Herein, clinical and preclinical evidence provided that stress-induced depressive pathology contributes to altered BDNF level and function in persons with MDD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
228
2
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 332 publications
(247 citation statements)
references
References 259 publications
(287 reference statements)
5
228
2
12
Order By: Relevance
“…Though stressful life events are not thought to be the cause of BD itself, they can be a trigger for recurrence. Whereas stress decreases brain‐derived neurotrophic factor (BDNF) and spine density in cognition‐related brain areas, such as the cerebral cortex and hippocampus, stress increases BDNF and spine density in the amygdala and nucleus accumbens, which are related to emotion . This suggests that stress causes remodeling of neural circuits to adjust the emotion/cognition (E/C) balance to adapt to stressful environments.…”
Section: Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though stressful life events are not thought to be the cause of BD itself, they can be a trigger for recurrence. Whereas stress decreases brain‐derived neurotrophic factor (BDNF) and spine density in cognition‐related brain areas, such as the cerebral cortex and hippocampus, stress increases BDNF and spine density in the amygdala and nucleus accumbens, which are related to emotion . This suggests that stress causes remodeling of neural circuits to adjust the emotion/cognition (E/C) balance to adapt to stressful environments.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Whereas stress decreases brain-derived neurotrophic factor (BDNF) and spine density in cognition-related brain areas, such as the cerebral cortex and hippocampus, stress increases BDNF and spine density in the amygdala and nucleus accumbens, which are related to emotion. 155,156 This suggests that stress causes remodeling of neural circuits to adjust the emotion/cognition (E/C) balance to adapt to stressful environments. In addition to antidepressants, 157 mood stabilizers 158 and atypical antipsychotics 159 also upregulate BDNF and possibly enhance plasticity.…”
Section: Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF is abundant in the central and peripheral nervous systems of humans and found in both the serum and plasma (Lee & Kim, 2010). BDNF is vital to survival, growth, and maintenance of neurons (Phillips, 2017). There has been strong evidence that neuroplastic mechanisms that involve BDNF are severely altered in individuals with depression (Phillips, 2017).…”
Section: Background On Growth Factorsmentioning
confidence: 99%
“…BDNF is vital to survival, growth, and maintenance of neurons (Phillips, 2017). There has been strong evidence that neuroplastic mechanisms that involve BDNF are severely altered in individuals with depression (Phillips, 2017). Specifically, clinical evidence has demonstrated that stress-induced depression has resulted in changes in BDNF expression and function, therefore altering neuroplasticity (Phillips, 2017).…”
Section: Background On Growth Factorsmentioning
confidence: 99%